The Panama Canal - Mann, Elizabeth, 1948-; Rangel, Fernando (New York : Mikaya Press, 1998)
Relates the history of how the Panama Canal was planned and built, including the political, international, and health aspects of getting the project finished on time
Includes index
Keywords: Panama Canal (Panama) -- History -- Juvenile literature